An Injectable Hydrogel with Excellent Self‐Healing Property Based on Quadruple Hydrogen Bonding. Issue 19 (25th August 2016) - Zhang, Guangzhao; Ngai, To; Deng, Yonghong; Wang, Chaoyang
Abstract : Injectable polymeric hydrogels with self‐healing property are extremely appealing in biomedical applications for the reason that they could be transplanted via direct injection, which causes minimal invasion to human body. This work presents a novel injectable hydrogel based on strong interaction of quadruple hydrogen bonding from ureido pyrimidinone (UPy) moieties. A new monomer ureido pyrimidinone‐diisocyanate‐2‐hydroxyethyl‐methylene acrylic ester (named UPy‐NMA) carrying UPy moiety is synthesized for the first time and copolymerized with acrylamide to prepare hydrogel copolymer (PAU). The hydrogel is prepared by dissolving corresponding copolymer into deionized water under certain conditions. Mechanical property of prepared hydrogel is measured by rheometer and the results show that the developed hydrogel display excellent self‐healing ability as well as outstanding injectable property. In addition, adequate pore size of hydrogels from scanning electron microscopy also hints that the fabricated hydrogel can provide an intriguing glimpse for potential applications of tissue engineering. Abstract : Injectable self‐healing polymeric hydrogels are prepared by copolymerizing acrylamide with UPy‐NMA. The new monomer UPy‐NMA bearing quadruple hydrogen bonding is synthesized and served as physical cross‐linking agent of prepared hydrogel. The fabricated hydrogel exhibits excellent self‐healing and injectable property which can provide an intriguing glimpse for potential applications of tissue engineering.